Pengaruh Penggunaan Metode Qiro'ati terhadap Minat Menjadi Hafidz dan Kemampuan Membaca Al-Qur'an - Fauji, Ilan Fahmi (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2023)
Learning to read the Qur'an in a number of Islamic educational institutions has started since a student is in an early age phase. One of the well-known methods of learning to read the Koran in our country is the Qiro'ati method. This study aims to determine the effect of the theory of learning the Qur’an using the Qiro'ati method on the interest in becoming a hafidz and the ability to read the Qur’an which has long been applied at Madrasah Diniyah Jami'atussakinah, Banjar City. The method used in this research is product moment correlation with one independent variable and two dependent variables. The results of the research show that there is a positive and not significant relationship between the qiro'ati method variable (X1) and the variable interest in becoming a hafidz (X2) together with the variable ability to read the Qur'an (Y). This is evidenced by the significance value or p (sig.) = 0.723 > 0.05 and a relationship value of 0.102. It shows. This means that there are other factors that affect the ability of students to read the Qur'an.